The Stress State of a Thick-Walled Hydraulic Press Cylinder with Concentrators - Lymarenko A.; Kurgan V.; Bazhanova A.; Khamray V.; Ponomarenko A.; Karabegović I. (Журнал інженерних наук)
The article deals with modeling and calculations of volumetric machine-building structures with complex geometry. The relevance of the work lies in the fact that its methodology and results can help design massive structural elements complex in shape, including cylinders of powerful hydraulic presses. Attention is paid to the problems of reducing the metal content of machine-building products and the safe conditions of their operation. Theoretical and applied work is based on numerical methods using analytical solutions to assess the reliability of computer calculation results. The choice of research method is because analytical solutions for massive parts of such a configuration are too complex for numerical implementation. Experimental methods are too expensive and not so universal as to sort out possible variants of shapes and sizes. For the actual model of the press, the capabilities of the finite element method implemented in the ANSYS multipurpose complex were selected and rationally used. The results of the calculations are summarized in the table and shown on the graphs of the stress distribution. Based on the performed calculations (with a reliability check based on the formulas of the theory of elasticity for simplified calculation schemes), conclusions were made to ensure a more even distribution of stresses and a reduction in the metal content of the product.